2022
DOI: 10.1007/s40204-022-00190-x
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of anti-bacterial cotton bandage using biologically synthesized nanoparticles for medical applications

Abstract: Recently the use of plant-derived extracts for the green synthesis of nanoparticles has drawn considerable attention. In the present study silver and copper nanoparticles were synthesized using extracts of Andrographis paniculata which is found to possess various pharmacological properties. The synthesized nanoparticles were characterized using UV spectroscopy, SEM with EDS, XRD, TEM and DLS. Furthermore, an attempt is made to impregnate these nanoparticles onto cotton bandages. The stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…The analysis of the silver nanoparticle content on the surface of cotton fabric based on EDS is shown in Table 6 and Figure 5. The peak at 3 keV confirmed the presence of the silver nanoparticles [26]. The amounts of silver nanoparticles decreased from before washing (3.70%) to after 20 and 30 washing cycles (2.48% and 1.63%, respectively), representing a reduction of 32.97% and 55.95% after washing.…”
Section: Antibacterial Property Of Silver Nanoparticles Coated Cotton...mentioning
confidence: 75%
See 1 more Smart Citation
“…The analysis of the silver nanoparticle content on the surface of cotton fabric based on EDS is shown in Table 6 and Figure 5. The peak at 3 keV confirmed the presence of the silver nanoparticles [26]. The amounts of silver nanoparticles decreased from before washing (3.70%) to after 20 and 30 washing cycles (2.48% and 1.63%, respectively), representing a reduction of 32.97% and 55.95% after washing.…”
Section: Antibacterial Property Of Silver Nanoparticles Coated Cotton...mentioning
confidence: 75%
“…Andrographis paniculata or green chiretta is an annual plant whose entire above-ground parts (leaves, flowers, and stems) can be used as a medicinal plant to treat common cold and fever [26]. The active ingredients include andrographolide, neoandrographolide, isoandrographolide, and 14-deoxyandrographolide [27].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the SPR band for silver nanoparticles obtained the absorbance peak at 430 nm, as reported in previous studies [ 14 ]. Similarly, Monika et al [ 4 ] reported that silver nanoparticles prepared using a plant extract exhibited a strong plasmon peak at 429 nm. The band intensity produced by silver nanoparticles was identified as a peak due to the surface plasmon resonance, which is an intrinsic property of metal band-based nanoparticles.…”
Section: Resultsmentioning
confidence: 98%
“…Nanoparticles have gained attention due to their unique morphological and physicochemical properties [ 3 ]. These metal nanoparticles possess strong inhibitory and antibacterial activity [ 4 ]. Iron nanoparticles have been widely applied in drug delivery and biomedical applications and possess toxicity against a broad spectrum of pathogenic bacteria and fungi [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…The emergence of antimicrobial resistance (AMR) pathogens complicates the treatment of bacterial and fungi infections, necessitating the development of novel approaches to address this global catastrophic threat . AMR has caused significant damage to numerous healthcare systems throughout the world, jeopardizing efforts to prevent and treat a variety of infectious diseases. , Starting from 2050, AMR might result in ten million deaths annually and could cost the entire world the approximate sum of 100.2 trillion US dollars .…”
Section: Introductionmentioning
confidence: 99%